2010
DOI: 10.1021/la904765u
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Amino Acids with the Au(111) Surface: Adsorption Free Energies from Molecular Dynamics Simulations

Abstract: Interactions of proteins with inorganic surfaces are of high importance in biological events and in modern biotechnological applications. Therefore, peptides have been engineered to recognize inorganic surfaces with high specificity. However, the underlying interactions are still not well understood. Here, we investigated the adsorption of amino acids as protein building blocks onto a Au(111) surface. In particular, using molecular dynamics simulations, we calculated the potential of mean force between all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
239
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(264 citation statements)
references
References 45 publications
24
239
1
Order By: Relevance
“…Juffer et al (1996) applied thermodynamic integration to compute the adsorption free energies of the enzyme cutinase and its variants to a charged surface in the presence of explicit ions. Hoefling et al (2010a) applied the method to obtain the PMF profiles of amino acids adsorbing on an Au(111) surface. Further, Schneider & Colombi Ciacchi (2010) employed thermodynamic integration, along with the umbrella sampling/WHAM method, to compare the free energy profiles of adsorption of RGD peptides on oxidized Ti obtained by the two methods.…”
Section: Equilibrium Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Juffer et al (1996) applied thermodynamic integration to compute the adsorption free energies of the enzyme cutinase and its variants to a charged surface in the presence of explicit ions. Hoefling et al (2010a) applied the method to obtain the PMF profiles of amino acids adsorbing on an Au(111) surface. Further, Schneider & Colombi Ciacchi (2010) employed thermodynamic integration, along with the umbrella sampling/WHAM method, to compare the free energy profiles of adsorption of RGD peptides on oxidized Ti obtained by the two methods.…”
Section: Equilibrium Methodsmentioning
confidence: 99%
“…This parameterization can be directly used in standard MM force-fields. The GolP FF has been applied in MD simulations of the adsorption of amino acids, as well as several proteins, on gold Cohavi et al 2011;Hoefling et al 2010aHoefling et al , b, 2011Kokh et al 2010). Furthermore, the ProMetCS (Kokh et al 2010) continuum solvent model describes proteinsurface interactions in atomic detail using the GolP Lennard-Jones interaction parameters together with an image charge model for protein-metal surface electrostatic interactions.…”
Section: Metal Surfacesmentioning
confidence: 99%
“…18,25,27,30,35,39,40 Here, AuBP2 sequence is rich in polar hydroxyl-containing (S, Y) amino acid residues, which have been previously reported to recognize the Au lattice. 25,26,35,41,42 Most recently, aromatic (Y, F, W) and basic amino acids (R, K) were computationally predicted and experimentally verified to adsorb to Au surfaces with even higher affinity and strength compared to traditional metal-binding amino acids (C, H). 41,43 Thus, the presence of aromatic and basic amino acids (W, Y, R) in AuBP2 potentially implies a novel gold-binding mechanism.…”
mentioning
confidence: 99%
“…25,26,35,41,42 Most recently, aromatic (Y, F, W) and basic amino acids (R, K) were computationally predicted and experimentally verified to adsorb to Au surfaces with even higher affinity and strength compared to traditional metal-binding amino acids (C, H). 41,43 Thus, the presence of aromatic and basic amino acids (W, Y, R) in AuBP2 potentially implies a novel gold-binding mechanism. At the same time, a lack of individual Cys and His amino acids eliminates the obvious well known metal-binding mechanisms by which peptides can attach non-specifically to metal surfaces.…”
mentioning
confidence: 99%
“…Although much of this work has been designed to isolate properties contributing to successful binding (e.g., flexibility, electrostatics, solvent interactions), it has remained difficult to distill this into a concise set of design principles. 36,53,54 In order to probe the origins of the predominance of hydroxyl-containing amino acids with gold surfaces, Calzolari et al 55 performed ab initio molecular dynamics (AIMD) of a hydroxyl containing b-sheet-forming peptide, and found that cooperativity between serine side chains and solvent molecules contributed to successful 57 suggested that Tyr, Met, and Phe are strong binders, while serine breaks through the hydration layer to form an anchor point. Verde et al 58 performed further molecular dynamics to study the role of flexibility and stability in adsorption of known gold-binding and non-gold-binding peptides.…”
Section: Gold-binding Peptidesmentioning
confidence: 99%